A specific gut microbiota and metabolomic profiles shifts related to antidiabetic action: The similar and complementary antidiabetic properties of type 3 resistant starch from Canna edulis and metformin. (September 2020) - Zhang, Chi; Ma, Shuangshuang; Wu, Jiahui; Luo, Linglong; Qiao, Sanyang; Li, Ruxin; Xu, Wenjuan; Wang, Nan; Zhao, Baosheng; Wang, Xiao; Zhang, Yuan; Wang, Xueyong
Graphical abstract: Highlights: Ce-RS3 showed anti-diabetic effects similar to those of metformin. Ce-RS3 and metformin have similarities in improving gut microbiota and serum metabolites. The beneficial effects of Ce-RS3 and metformin may be associated with host-microbiota interactions. This study prompted us to suggest possible "Drug-Dietary fiber" combinations for managing T2DM. Abstract: The relationship between gut microbiota and type 2 diabetes mellitus (T2DM) has drawn increasing attention, and the benefits of various treatment strategies, including nutrition, medication and physical exercise, maybe microbially-mediated. Metformin is a widely used hypoglycemic agent, while resistant starch (RS) is a novel dietary fiber that emerges as a nutritional strategy for metabolic disease. However, it remains unclear as to the potential degree and interactions among gut microbial communities, metabolic landscape, and the anti-diabetic effects of metformin and RS, especially for a novel type 3 resistant starch from Canna edulis (Ce-RS3). In the present study, T2DM rats were administered metformin or Ce-RS3, and the changes in gut microbiota and serum metabolic profiles were characterized using 16S-rRNA gene sequencing and metabolomics, respectively. After 11 weeks of treatment, Ce-RS3 exhibited similar anti-diabetic effects to those of metformin, including dramatically reducing blood glucose, ameliorating the response to insulin resistance and glucose tolerance test, and relieving the pathological damage in T2DM rats. Interestingly, the microbial and systemic metabolic dysbiosis in T2DM rats was effectively modulated by both Ce-RS3 and, to a lesser extent, metformin. The two treatments increased the gut bacterial diversity, and supported the restoration of SCFA-producing bacteria, thereby significantly increasing SCFAs levels. Both treatments simultaneously corrected 16 abnormal metabolites in the metabolism of lipids and amino acids, many of which are microbiome-related. PICRUSt analysis and correlation of SCFAs levels with metabolomics data revealed a strong association between gut microbial and host metabolic changes. Strikingly, Ce-RS3 exhibited better efficacy in increasing gut microbiota diversity with a peculiar enrichment of Prevotella genera. The gut microbial properties of Ce-RS3 were tightly associated with the T2DM-related indexes, showing the potential to alleviate diabetic phenotype dysbioses, and possibly explaining the greater efficiency in improving metabolic control. The beneficial effects of Ce-RS3 and metformin might derive from changes in gut microbiota through altering host-microbiota interactions with impact on the host metabolome. Given the complementarity of Ce-RS3 and metformin in regulation of gut microbiota and metabolites, this study also prompted us to suggest possible "Drug-Dietary fiber" combinations for managing T2DM.